Formulation, gastrointestinal transit studies and absorption of amphotericin B-containing solid lipid nanoparticles in rats - Amekyeh, Hilda (2016)
Successful delivery of pharmaceuticals orally requires a firm understanding of how dosage forms behave during their passage through the gastrointestinal (GI) tract. In this study, the GI transit time and absorption of amphotericin B (AmB) solid lipid nanoparticles (SLN) were investigated in rats, using paracetamol (PAR) and sulphapyridine (SP) as indirect markers. A high encapsulation efficiency of 91.2% was obtained for the AmB SLNs. The SLNs were exhaustively characterised with regards to size, zeta potential (ZP), viscosity, density, migration propensity within agarose gel, in vitro drug release and morphology, to ensure similar disposition in the GI tract after simultaneous oral administration. Freeze-drying did not significantly alter the size or ZP of the AmB SLNs, and in vitro drug release from fresh and freeze-dried SLNs were identical. AmB, PAR and sulphasalazine (SSZ) (the latter being the prodrug of SP) were individually formulated into SLNs using beeswax and theobroma oil as the lipid matrix. The z-averages, polydispersity indices and ZPs of the SLNs ranged from 206.5-224.8 nm, 0.161-0.218 and |61.90|-|71.90| mV, respectively. Gel electrophoresis studies indicated a similar movement propensity among the three SLNs as their migration distances were identical (22.2-22.4 mm) within agarose gel. Scanning electron and atomic force microscopy studies revealed that all three SLNs were spherical in morphology and with similar surface characteristics. The SLNs were assessed for changes in size and surface charge on exposure to simulated GI fluids using dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA). On contact with the fluids, the particles had a slight increase in size due to ingress of the dissolution media. NTA results were found to be more beneficial than DLS as the latter was biased towards larger particles that were present possibly due to aggregation. After incubation in simulated gastric fluid followed by simulated intestinal fluid (mimicking gastric emptying), all the SLNs were found to be less than 350 nm in size and neutral in charge, which are optimal attributes for intestinal absorption. Time-of-flight secondary ion mass spectroscopic (ToF-SIMS) analyses revealed minimal drug amounts on the surfaces of the particles indicating that drug location was in the core of the SLNs. A developed and validated high-performance liquid chromatography (HPLC) method for simultaneous assay of the drugs in rat plasma using piroxicam as internal standard was found to be sensitive, accurate and precise, with drug recovery from plasma exceeding 92% in each case. A pilot GI transit study conducted in rats showed that the HPLC method was appropriate for the study. In the main study, the effects of food on the transit and absorption of the AmB SLNs were investigated. The presence of food slowed the transit of the SLNs in the GI tract. The gastric transit time of the AmB SLNs was estimated indirectly using PAR and was obtained as 1.71-2.25 hr. Caecal arrival time (CAT) of the AmB SLNs was estimated using SP detection in plasma as SSZ metabolism to produce SP occurs predominantly by the activity of colonic flora. In both fasted and fed states, CAT was 1.80-1.90 hr whereas transit time through the small intestine was 1.65-1.79 hr. A delayed rate of AmB absorption was observed in the fed state however, the extent of absorption was not affected by food. The percentage AmB absorption during the fasted state in the stomach, small intestine and colon were not significantly different from absorption within the respective regions in the fed state. In both states however, absorption was highest in the colon and appeared to be a summation of small intestinal absorption plus absorption proper within the colon. The study indicated that, AmB SLNs irrespective of food status were slowly but predominantly taken up via the lymphatic route and the small intestine was the most favourable site for their absorption. The data obtained indicate that it is possible to enhance the bioavailability of AmB through its incorporation into SLNs. Further enhancement of AmB bioavailability can be achieved through appropriate formulation interventions aimed at slowing transit of the SLNs in the small intestine. Finally, being a lipid-based system, the SLNs may have a potential to reduce the nephrotoxic effects of AmB.